Observation of initial clinical manifestations and repercussions from the treatment of 314 human injuries caused by black sea urchins (Echinometra lucunter) on the southeastern Brazilian coast - Haddad Júnior, Vidal [UNESP] (Sociedade Brasileira de Medicina Tropical - SBMT, 2012)
INTRODUÇÃO: Os acidentes causados por ouriços-do-mar são as ocorrências por animais marinhos mais comuns no país. O ouriço-do-mar preto (Echinometra lucunter) é a espécie que mais causa ferimentos em banhistas. MÉTODOS: Este trabalho registrou e estudou 314 agravos com ênfase nas manifestações clínicas iniciais observadas e suas implicações na terapêutica recomendada. RESULTADOS: Todos os acidentes foram causados pelo ouriço-do-mar preto e aconteceram em banhistas. As lesões e a dor foram associadas ao trauma causado pela penetração das espículas (não ocorreu inflamação ou dor imediata sem pressão sobre os pontos comprometidos). As complicações deste tipo de acidente, incluindo infecções e granulomas de corpo estranho, estão associadas com a permanência das espículas nos ferimentos. CONCLUSÕES: Foi confirmado o fato do acidente causado por esta espécie ser o mais comum no Brasil e apresentar caráter traumático, sendo a principal recomendação a retirada precoce dos espinhos para prevenção de complicações tardias como as infecções e formação de granulomas de corpo estranho.

INTRODUCTION: Injuries caused by sea urchins are the most common caused by marine animals in humans in Brazil, with the black sea urchin (Echinometra lucunter) causing the most injuries to bathers. METHODS: This study observed 314 human wounds with emphasis on the early observation of clinical signs and symptoms and their implications on the recommended treatment. RESULTS: All the injuries were caused by black sea urchins and were observed in bathers. The lesions and the pain were associated with penetration of the spines; there was no early inflammation or pain without pressure on the wounded places. Complications arising from this kind on injury, including infections and foreign body granulomas, are associated with the permanence of the spines in the wounds. CONCLUSIONS: The study confirmed that this kind of injury is the most common accident caused by aquatic animals in Brazil. The main therapeutical recommendation is early removal of the spines to prevent late complications, such as infections and the formation of foreign body granulomas.
Observação das manifestações clínicas iniciais e sua influência no tratamento de 314 acidentes causados por ouriços-do-mar pretos (Echinometra lucunter) na região sudeste do Brasil
Keywords: Animais aquáticos perigosos; Ouriço-do-mar preto; Echinometra lucunter; Brasil; Dangerous aquatic animals; Black sea urchin; Echinometra lucunter; Brazil